2019
DOI: 10.1016/j.ecoser.2019.100898
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem services in the Arctic: a thematic review

Abstract: The study presents the first systematic review of the existing literature on Arctic ES. Applying the Search, Appraisal, Synthesis and Analysis (SALSA) and snowballing methods and three selection criteria, 33 publications were sourced, including peer-reviewed articles, policy papers and scientific reports, and their content synthesised using the thematic analysis method. Five key themes were identified: (1) general discussion of Arctic ES, (2) Arctic socialecological systems, (3) ES valuation, (4) ES synergies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 75 publications
1
45
0
Order By: Relevance
“…An estimated 12.9 km 3 cubic kilometers of saline groundwater exists in comparison to about 10.5km 3 of fresh groundwater (Gleick,1996), with direct impacts for water supply and socio-economic services of the resource. Despite the low attention to sea-ice biomes degradation in relation to the terrestrial and marine biomes, as previously observed (Malinauskaite et al, 2019), today there is increasing concern over the threats to ice caps. The ecosystem services related to climate regulation and biodiversity provided by ice caps are becoming of vital importance for the planet.…”
Section: Current Threats To Freshwater and Ecosystem Servicesmentioning
confidence: 94%
See 1 more Smart Citation
“…An estimated 12.9 km 3 cubic kilometers of saline groundwater exists in comparison to about 10.5km 3 of fresh groundwater (Gleick,1996), with direct impacts for water supply and socio-economic services of the resource. Despite the low attention to sea-ice biomes degradation in relation to the terrestrial and marine biomes, as previously observed (Malinauskaite et al, 2019), today there is increasing concern over the threats to ice caps. The ecosystem services related to climate regulation and biodiversity provided by ice caps are becoming of vital importance for the planet.…”
Section: Current Threats To Freshwater and Ecosystem Servicesmentioning
confidence: 94%
“…Attractiveness of surface freshwater ecosystems and their biodiversity richness attract visitors, sport practitioners and nature lovers, bearing clear benefits to their physical, mental and psychological well-being. The presence of surface water bodies and the contact with biodiversity are considered to provide health benefits, thus improve mental, spiritual, cultural, and physical health(Völker and Kistemann, 2013;McFarlane et al, 2019) and even increase property prices(Apostolaki and Jefferies, 2009;Venohr et al, 2018), at occasionally high levels.…”
mentioning
confidence: 99%
“…Terrestrial ecosystems, especially in the northern high latitude (NHL) area, are predicted to undergo substantial impacts associated with changes of land use and climate in the next several decades (Warszawski et al 2013, IPCC 2014. Such changes in terrestrial ecosystems are likely to influence human societies through deterioration of ecosystem services such as climate regulation, recreational services, and provision of foods and goods (Malinauskaite et al 2019). Moreover, the fact that changes in ecosystem structures and functions are highly likely to exert climatic feedbacks on the human-induced warming (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, most biomes have had multiple ES values estimated (Costanza et al 1997; Costanza et al 2014; de Groot et al 2012) with global annual ecosystem services values calculated at over $100 trillion dollars a year (de Groot et al 2012; Costanza et al 2014). However, two biomes that cover a large proportion of the terrestrial surface remain relatively understudied: desert and tundra (Malinauskaite et al 2019). Taylor et al (2017) developed a valuation for a portion of the Chihuahuan Desert and O’Garra (2017) has provided an estimate of some key ecosystem services for Arctic tundra.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the circumpolar region is estimated to contain large quantities of oil and gas, up to 22% of the global reserves (Bird et al 2008), enhanced fossil fuel extraction could further exacerbate climate change. Currently, there is little information on how ES relate to management of specific Arctic regions (Malinauskaite et al 2019)…”
Section: Introductionmentioning
confidence: 99%